On Weyl Multipliers of Almost Everywhere Unconditional Convergence of Series With Respect to General Haar and Franklin Systems - Barkhudaryan, Rafayel; Gevorkyan, Gegham (Armenian Journal of Mathematics, 2026)
We obtain necessary and sufficient conditions for an increasing nonnegative sequence ω_n, nN, to be a Weyl multiplier for a.e. unconditional convergence for general Haar or Franklin systems corresponding to an admissible sequence T.